REINTERPRETASI KONSEP BERMEDIA SOSIAL DALAM AL-QUR’AN: UPAYA PENGUATAN KARAKTER KAUM MILENIAL DI ERA POST TRUTH - Helmina; Ican Mandala (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2024)
In the post-truth era, science and technology have undergone significant advancements. Technology has come to dominate various aspects of life. Social media is a positive outcome of technological progress, facilitating information acquisition and communication. However, alongside these benefits, the negative impacts of technological advancements are inevitable. For instance, social media platforms are often used to spread false news, hate speech, fraud, and other malicious activities. Such phenomena undoubtedly influence the character of the younger generation, who are predominantly active on social media. Young social media users, in particular, are more susceptible to these negative effects. This presents a challenge for social media users. To mitigate the rapid spread of these issues, a reinterpretation of the concept of social media usage as articulated in the Qur'an is necessary. In this study, the author employs a library research method to analyze the data. The data analyzed includes books, articles, journals, magazines, and other sources. Additionally, the author collects various verses from the Qur'an and Hadiths relevant to the topic. This research aims to elucidate the role of social media in strengthening the character of the Muslim generation. By adopting this concept, it is possible not only to shape the character of the Muslim youth but also to establish an ethical framework for social media use. Consequently, Muslim youths can critically evaluate the information disseminated through social media. Ultimately, social media can become a platform for spreading goodness and fostering the growth of Islam.